Role of Transcatheter patent ductus arteriosus closure in extremely low birth weight infants. Issue 1 (30th September 2018) - Sathanandam, Shyam; Balduf, Kaitlin; Chilakala, Sandeep; Washington, Kristen; Allen, Kimberly; Knott‐Craig, Christopher; Rush Waller, Benjamin; Philip, Ranjit
Abstract: Background: Patent ductus arteriosus (PDA) is common in extremely low birth weight (ELBW) infants. The objectives of this study were to describe our early clinical experience of transcatheter PDA closure (TCPC) in ELBW infants, compare outcomes with surgical ligation of PDA (SLP), and identify risk factors for prolonged respiratory support. Methods: A retrospective review was performed comparing infants born <27 weeks, weighing <1 kg at birth and < 2 kg during TCPC with 2:1 propensity‐score matched group of infants that underwent SLP. Change in respiratory severity scores (RSS) immediately post‐procedure and the time taken for return to pre‐procedure RSS for TCPC versus SLP was compared. Factors contributing to prolonged elevation of RSS were identified. Results: Eighty ELBW infants (median procedure weight: 1060 [range 640–2000] grams) that underwent successful TCPC were compared with 40 infants that underwent SLP (procedure weight 650–1760 g). There was greater increase in RSS following SLP compared to TCPC (76% vs. 18%; P < 0.01). It took longer for RSS to return to pre‐procedural scores post‐SLP compared to post‐TCPC (28 vs. 8.4 hr; P < 0.01). Elevated pulmonary artery pressure (PAP) and TCPC at >8 weeks of age were associated with prolonged (>30‐days) elevation of RSS ≥ 1 (OR = 5.4, 95%CI: 2.2–9.4, P < 0.01 and OR = 2.86, 95%CI: 1.5–4.2, P = 0.05 respectively). Overall complication rate for TCPC was 3.7%. Conclusions: TCPC is feasible in infants as small as 640‐2000 g and can be performed safely in the majority. TCPC may offer faster weaning of respiratory support compared to SLP when performed earlier in life, and before the onset of elevated PAP.